National Identity in Global Cinema - Celli, C. author. aut Link
IX, 178 p. 10 illus.
Keywords: When themes of historical and cultural identity appear and repeat in popular film, it is possible to see the real pulse of a nation and comprehend a people, their culture and their history. National Identity in Global Cinema describes how national cultures as reflected in popular cinema can truly explain the world, one country at a time.